Respuesta :

Answer:

no

Step-by-step explanation:

equate the two equations (make them equal to each other)

-2/5x - 7 = 2/5x - 3

get rid of the fractions by multiplying everything by 5

5(-2/5x - 7 = 2/5x - 3)

-2x - 35 = 2x - 15

solve

-2x - 35 = 2x - 15

-2x - 2x = -15 + 35

-4x = 20

x = -5

plug in "x" to one of the starting equations (I'm using the second one)

y = 2(-5) - 15

y = -10 - 15

y = -25

an easier way would be to plug in the point for "x" and "y"

-5 = 2(-5) - 15

-5 = -10 - 15

-5 = -25            FALSE

ACCESS MORE